Accurate fixation of plates and screws for the treatment of acetabular fractures using 3D-printed guiding templates: An experimental study. Issue 6 (June 2017) - Chen, Xu; Chen, Xuanhuang; Zhang, Guodong; Lin, Haibin; Yu, Zhengxi; Wu, Changfu; Li, Xing; Lin, Yijun; Huang, Wenhua
Abstract: Objective: To investigate the feasibility of the use of 3D-printed guiding templates for accurate placement of plates and screws for internal fixation of acetabular fractures. Methods: 3D models of the pelvises of 14 adult cadavers were reconstructed using computed tomography (CT). Twenty-eight acetabular fractures were simulated and placement positions for plates and screw trajectories were designed. Bending module was obtained by 3D cutting; guiding template was manufactured using 3D printing, and the plate was pre-bent according to the bending module. Plates and screws were placed in cadaveric pelvises using the guiding template, and 3D model was reconstructed using CT. The designed and real trajectories were matched using 3D registration including the coordinates (entry and exit points) of designed trajectory. The number of qualified points with different accuracy levels was compared using Chi-squared test. Results: Sixty-four plates and 339 screws were placed with no cortical breach. The absolute difference of the X, Y, and Z coordinates between the designed and real entry points were 0.52 ± 0.45, 0.43 ± 0.36, and 0.53 ± 0.44 mm, respectively. The corresponding values for the exit points were 0.83 ± 0.67, 1.22 ± 0.87, and 1.26 ± 0.83 mm, respectively. With an accuracy degree ≥1.9 mm for the entry points and ≥3.8 mm for the exit points, there was no significant difference between the designed and the real trajectories. Conclusion: The 3D-printed guiding template helped achieve accurate placement of plates and screws in the pelvis of adult cadavers.